Autoantibodies and the Immune Hypothesis in Psychotic Brain Diseases: Challenges and Perspectives. (24th August 2013) - Pathmanandavel, Karrnan; Starling, Jean; Dale, Russell C.; Brilot, Fabienne
Abstract : The pathophysiology of psychosis is poorly understood, with both the cognitive and cellular changes of the disease process remaining mysterious. There is a growing body of evidence that points to dysfunction of the immune system in a subgroup of patients with psychosis. Recently, autoantibodies directed against neuronal cell surface targets have been identified in a range of syndromes that feature psychosis. Of interest is the detection of autoantibodies in patients whose presentations are purely psychiatric, such as those suffering from schizophrenia. Autoantibodies have been identified in a minority of patients, suggesting that antibody-associated mechanisms of psychiatric disease likely only account for a subgroup of cases. Recent work has been based on the application of cell-based assays—a paradigm whose strength lies in the expression of putative antigens in their natural conformation on the surface of live cells. The responsiveness of some of these newly described clinical syndromes to immune therapy supports the hypothesis that antibody-associated mechanisms play a role in the pathogenesis of psychotic disease. However, further investigation is required to establish the scope and significance of antibody pathology in psychosis. The identification of a subgroup of patients with antibody-mediated disease would promise more effective approaches to the treatment of these high-morbidity conditions.